Chest physiotherapy in children with acute bacterial pneumonia - Lieselotte Corten; Jennifer Jelsma; Brenda M. Morrow (AOSIS, 2015)
Background: Pneumonia is the single leading cause of death in children younger than 5 years of age. Chest physiotherapy is often prescribed as an additional therapy in children with pneumonia. Different chest physiotherapy techniques are available that aim to improve airway clearance, gas exchange and reduce the work of breathing. However, it is unclear if these techniques are effective in this population. Objective: The present review aimed to determine the efficacy of different chest physiotherapy techniques compared with no physiotherapy or other chest physiotherapy treatments in hospitalised children with bacterial pneumonia. Method: Six electronic databases (PubMed, Medline, Cochrane Library, PEDro, CINAHL and Africa-wide information), clinicaltrials.gov and pactr.org were searched for eligible studies. Results: Two randomised controlled trials and one ongoing study were identified. Neither completed trial reported differences between the control and intervention groups, although one study reported a longer duration of coughing (p = 0.04) and rhonchi (p = 0.03) in the intervention group. Conclusion: Because of the limited number of included articles and different presentations of outcome measures, we could not reject or accept chest physiotherapy as either an effective or harmful treatment option in this population.